2015
DOI: 10.21863/ijbai/2015.3.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Efficiency of Marketing Efforts in the Indian Pharmaceutical Industry using Data Envelopment Analysis

Abstract: Pharmaceutical companies have been spending huge amount of money on marketing and promotions, sales distribution, and traveling done by the sales representatives. However, they find it difficult to directly link the returns with these efforts. This study makes an attempt to examine whether the marketing efforts have significant influence on the sales performance in the industry. It uses the DEA model (Data Envelopment Analysis) to assess the efficiency of marketing efforts by pharmaceutical companies, and uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Researchers have identified relationship marketing, social media impact, market promotion, R&D intensity, strategic account management, price regulations, mergers, capital structure, and financing decisions as some of the business functional factors influencing the performance of PSC (Bhardwaj et al, 2010;Desai & Desai, 2018;Dash et al, 2015;Enyinda et al, 2018;Golec & Vernon, 2010;Sil, 2015;Sharma, 2012). Among the functional factors, research showed that marketing-mix components effectively limited the influence of generic pharmaceutical brands (Wilkie et al, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Researchers have identified relationship marketing, social media impact, market promotion, R&D intensity, strategic account management, price regulations, mergers, capital structure, and financing decisions as some of the business functional factors influencing the performance of PSC (Bhardwaj et al, 2010;Desai & Desai, 2018;Dash et al, 2015;Enyinda et al, 2018;Golec & Vernon, 2010;Sil, 2015;Sharma, 2012). Among the functional factors, research showed that marketing-mix components effectively limited the influence of generic pharmaceutical brands (Wilkie et al, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%